Agresivitas Pelaporan Keuangan, Pertumbuhan Penjualan, Intensitas Modal, dan Agresivitas Pajak: Kepemilikan Intitusional Sebagai Variabel Moderasi - Rafiyudin Wahid (Jurnal Literasi Akuntansi, 2021)
Purpose: This study aims to prove the financial reporting aggressiveness, sales growth, and capital intensity towards tax aggressiveness with institutional ownership as moderating variable.Method: The analysis method study used is multiplier inear regression, data were analyzed using Moderated regression (MRA), and data tool test using SPSS software. The population study are focusing on manufacturing companies listed in Indonesia Stock Exchange in the period 2016-2019. The sampling method by purposive sampling of 112 samples. The data obtained from the website of Indonesia Stock Exchange (www.idx.co.id).Finding: The results showed that the financial reporting aggressiveness had a positive effect on tax aggressiveness, sales growth had a positive effect on tax aggressiveness, capital intensity growth had a negative effect on tax aggressiveness, institutional ownership as the moderating variable weakened the influence of aggressive financial reporting on tax aggressiveness, institutional ownership as the moderating variable strengthened the influence of sales growth, and capital intensity on tax aggressiveness.Novelty: This study used is Cash Effective Tax Rate (CETR) to measure tax aggressiveness and the addition of moderating variables.